Juvenile Detention and Correctional Facility Census, 1971 ([Verlag nicht ermittelbar], 1984)
The purpose of this census was to provide information on juvenile detention centers throughout the United States. The data include information on type of facility, level of government administering the facility, resident population by sex, by age range, by detention status, and by offense, admissions and discharges, average length of stay, staffing and expenditures, age and capacity of facility, and programs and services available.